The Effect of Mind Maps in Malay Language Essays on Form Four Students - Jessica Serang; Saripah Banseng; Md Noor Saper (Peneliti.net, 2022)
This research was conducted to identify the understanding of Form Four students and analyze the differences in mean achievement between the control and experimental groups on the mind map of Malay essays. This selection map was tested on 30 Form Four students at SMK Bahasa Malaysia, Saratok. Statistics were collected through the survey and quasi-experimental methods, and the peeled data was done quantitatively. The findings of this study show that the level of understanding of Form Four students is at a moderately high level because most students know the names and functions of each mind map introduced. Furthermore, the mean of post-test students taught using mind maps was higher than that taught using cooperative learning, which was a 1.8 difference. The increase in the experimental group's mean in this post-test showed that teaching Malay essays using mind maps improved student achievement in writing essays. This research can help Malay language teachers diversify their teaching techniques and help students master the writing of Malay language essays.